An Empirical Analysis of Impact of Foreign Aid on Economic Growth: The Case of Pakistan - Akram, Muhammad; ., Mahpara (Information Management and Business Review, 2011)
The objective of this study is to analyze the effects of foreign aid on economic growth of Pakistan. The time series data for the period 1980-2008 is used by applying OLS regression model and two diagnostic methods namely Breusch-Pagon and Durbin-Watson tests. Results depict that foreign aid is insignificantly related to the economic growth to Pakistan for short-run and long-run. By excluding the foreign direct investment, results are significant but still a negative relationship exists. This study will help to government organizations by recognizing about the impact of foreign aid on economic growth.